ID259 Conhecimento e prevalência do uso de cigarros eletrônicos entre estudantes e residentes da saúde em Hospital de Referência no Amazonas: um estudo transversal: EIXO 3: EQUIDADE E ACESSO - Silva de Paula Soares, Luiz Alexandre; Lins Gonçalves, Roberta (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2024)
Introdução Quitting smoking is one of the promises made by many Brazilians. Some want to do it, but can’t, others think that smoking doesn’t do that much harm and there are also people who live with smokers and don’t know the risks they may be facing. The health damage caused by tobacco smoke is well known to both health professionals and the general public. While the numbers of smokers of traditional cigarettes are declining, the number of users of new smoking devices, such as electronic cigarettes, is growing rapidly. These electronic smoking devices have been presented as an option to aid smoking cessation, however they have been shown to have several harmful effects. It is imperative that the prevalence of e-cigarette use among health students is known, as future health professionals have the task of looking after and promoting their own health and that of their future patients. Based on the above, the aim of this study was to estimate the prevalence of e-cigarette use by doctors, residents and medical students at a university hospital. Métodos To this end, a cross-sectional observational study was carried out and data was obtained using a semi-structured online questionnaire on Google Forms. The normality of the age variable was checked using the Shapiro-Wilks statistical test. The nominal qualitative variables were presented in tables using absolute and relative frequencies. The relationship between risk factors (or antecedents) and e-cigarette use was checked using the chi-square or Fisher’s exact test, with the decision rule based on a 5% significance level. Resultados A total of 36 people took part in the study. The majority of participants were women with 21 responses (58.3%). The majority of participants were medical students with 25 responses (69.4%). Regarding smoking in the family, 13 people reported having smokers in the family. 91.7% said they knew about e-cigarettes and the same number said they believed e-cigarettes were bad for their health, but 44.4% said they had already tried them. The majority (87.5%) of this group who had used e-cigarettes smoked with friends. A positive association was found between the presence of smokers in the family and e-cigarette use (p = 0.052), but no other statistically relevant relationship was found in our preliminary data. Discussão e conclusões The results showed that, despite the fact that the sample studied was aware of the potential risks of using electronic cigarettes, a significant proportion still uses this device. The majority of the sample who reported using e-cigarettes were medical students, most of whom were young women who used e-cigarettes recreationally. It is important to emphasize that these results are preliminary with a low sample size, so the power of the study was diminished, but these results will help with new knowledge to understand this important problem, since the health professional who smokes destroys all credibility of the message that smoking is harmful to health and hastens death, discrediting the fight against smoking.